Factors predicting the mathematics anxiety of adolescents: a structural equation modeling approach - Ahmmed, Suman; Saha, Jashodhan; Tamal, Maruf Ahmed; Abdullah Al Mamun, Khondaker; Islam, Sajani (Frontiers in Psychiatry, 2024)
IntroductionMathematics anxiety (MA) is a distinct negative emotional state or trait that individuals experience when confronted with mathematical problems in everyday life and academic contexts. This study aims to identify the key predictors of MA among secondary-level students in Bangladesh.MethodsUtilizing a quantitative cross-sectional research design, data were collected from 486 students across 89 institutions. Later, the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).ResultsThe findings revealed that math related negative past experiences (β = 0.241, t = 4.914, p < 0.001) and a perceived lack of teacher support (β = 0.234, t = 5.440, p < 0.001) significantly contribute to students’ low self-efficacy in mathematics. This low self-efficacy is further influenced by negative attitudes and test anxiety, ultimately leading to increased MA (β = 0.694, t = 22.695, p < 0.001). Additionally, cognitive challenges, particularly working memory difficulties, directly affect MA (β = 0.110, t = 2.659, p = 0.008). The study also found that negative attitudes (β = 0.347, t = 9.063, p < 0.001) and test anxiety (β = 0.251, t = 5.913, p < 0.001) independently exacerbate MA. Moreover, a lack of motivation in learning mathematics is directly influenced by this elevated level of MA (β = 0.384, t = 9.939, p < 0.001).DiscussionTaken together, the study proposes several key recommendations and policy implications to inform the development of synchronized policies by educational authorities aimed at combatting, reducing MA among secondary-level students in Bangladesh and similar contexts.